Optimization of Coffee-Gelatin Shot Formulations Based on Physicochemical, Rheological and Sensory Properties Using Response Surface Methodology - Sotomayor Vinan, Pablo Andres; Ruparel, Monik Manish; Tandukar, Resha; Mitra, Pranabendu (Journal of Food Industry, 2024)
The objective of this study was to optimize the coffee content and alcohol content of the formulations of coffee-gelatin shots based on physicochemical, rheological and sensory properties of the products. Because the coffee content and alcohol content influenced those properties of coffee-gelatin shots significantly which were related to the consumers’ acceptance. Thirteen different coffee-gelatin shots for nine formulations based on CCRD were developed and the sensory properties (overall acceptability, color, flavor and texture), L-value, pH and viscosity of coffee-gelatin shots were determined. The regression models were developed to predict the response variables as a function of independent variables. The response surface models were developed to understand the effects of independent variables on the responses. A desirability function was used to determine an optimum formulation using a numerical optimization technique. All contour plots of response surface models were superimposed to visualize an optimum region. The regression models could predict the sensory properties, L-value, pH and viscosity of coffee-gelatin shots as a function of coffee content and alcohol content with an accuracy of 77-99% depending on the properties of coffee-gelatin shots. The coffee content and alcohol content affected the sensory properties, L-value and viscosity of coffee-gelatin shots significantly (p<0.05). The optimization results obtained using numerical and graphical optimization techniques indicated that a combination of coffee (2.50 -3.00 g) and alcohol (5.25-6.75 mL) was the optimum formulation of a coffee-gelatin shots that improved the sensory properties, L-value, pH and viscosity of the coffee-gelatin shots. This optimum formulation of coffee-gelatin shots is expected to be useful for commercial manufacturing of consumers’ desired coffee-gelatin shots.